Tissue culture, biological activities and In Vitro flowering of Oxalis Triangularis / Anis Idayu binti Mad Yussof - Mad Yussof, Anis Idayu (2013)
Oxalis triangularis (A.St.-Hil) or commonly known as ‘Pokok Rama-rama’ in Malaysia is a beautiful ornamental plant which is propagated by bulbs. The plant grows to a height of 0.1 m - 0.2 m and is perfect for cultivating in pots or containers. Nowadays, with the emerging and advanced technologies, an efficient protocol has been established for a rapid multiplication of Oxalis triangularis in a large scale production under aseptic conditions. In vitro plant regeneration of Oxalis triangularis was successfully obtained in the present study via petiole and leaf as explants. The petiole explants cultured on MS medium supplemented with 0.5 mg/l α-Naphthaleneacetic acid (NAA) and 1.0 mg/l Kinetin (KIN) produced maximum number of adventitious shoots (12 shoots) while for leaf explants, the best treatment achieved on MS medium supplemented with 1.0 mg/l NAA and 1.5 mg/l 6-Benzylaminopurine (BAP) which produced a maximum of 14 shoots within 8 weeks. Comparison between in vivo plants and in vitro was observed using a Scanning Electron Microscope. The morphological features for both petiole and leaf samples have no differences. Both contain same structures of stomata and trichomes. In vitro flowering which is very important in order to improve quality and shortened physiological process of flowering was observed when adventitious shoots explants cultured on MS medium supplemented with 0.5 mg/l NAA and 0.5 mg/l BAP (90% in vitro flowering). In the synthetic seeds study, two different storage durations were tested (Day 7 and Day 30). The highest frequency of synthetic seeds production in Oxalis triangularis was recorded on Day 7 with 96.67% of conversion frequency. The number of shoots per encapsulated bead was 4.57 ± 0.72 with 100% roots emergence. Synthetic seeds were also sown on black soil and sterile black soil. However, both soil conditions gave negative results due to fungal infection. For the biological activities study, anthocyanin from petiole and leaf explants could be extracted by acidified methanol and acidified acetone solvents, and subsequently by reading the absorbance of UV-visible spectrophotometer. The highest anthocyanin absorbance for in vivo and in vitro petiole explants were recorded from explants extracted in acidified acetone solvent at concentration of 5 ml with the reading of 1.093 and 0.968, respectively. Different results were obtained for leaf explants in in vivo and in vitro. In vivo leaf explants showed highest anthocyanin pigment when extracted with acidified acetone at solvent concentration of 20 ml with absorbance of 2.223, meanwhile, in vitro leaf explants in acidified acetone at solvent concentration of 50 ml with absorbance of 1.280. Extraction was further examined with the natural pigment for paint production. Extraction from in vitro leaf explants had more dense colours compared to in vitro petiole explants. Extraction of in vitro leaf explants was coated on glass slides and let to dry overnight before being subjected to weathering tests; heat and salt tests. Both weathering tests had shown similar results whereby, it caused degradation of anthocyanin pigment. In phytochemical screening of Oxalis triangularis, four different solvents were used to test the presence of terpenoids/steroids, tannins, saponins, reducing sugar and glycosides. Both in vivo and in vitro plant extract only revealed the presence of steroids and saponins. In the antioxidant activity, both explants (in vivo and in vitro) of Oxalis triangularis in methanolic extracts were evaluated using DPPH free radical scavenging activity. In vitro petiole in methanolic extracts showed the lowest reading of IC50 value (less than 20μg/ml), among all the extracts that indicated the higher of inhibition rate. In vitro plantlets obtained from leaf explants were acclimatized in the greenhouse. Three types of growing substrates (black soil, red soil and vermiculite) were tested to identify the best soil to grow Oxalis triangularis successfully. The present study showed that all the growing substrates (black soil, red soil and vermiculite) tested could be used to grow Oxalis triangularis but the recommended soil would be black soil because it resulted in high survival rates and low fungal infections.